Clinical Characteristics of Transient Ischemic Attack Patients with Atrial Fibrillation: Analyses of a Multicenter Retrospective Study - Hama, Yuka (Cerebrovasc Dis Extra, 2015)
BACKGROUND: Atrial fibrillation (AF) is an important risk factor for transient ischemic attack (TIA). However, little is known about the characteristics of TIA patients with AF. This study investigated the characteristics of such patients, using data from a retrospective, observational, multicenter study. METHODS: TIA patients admitted to 13 stroke centers in Japan within 7 days of onset between January 2008 and December 2009 were included. The present analyses compared baseline characteristics, clinical symptoms, findings from diffusion-weighted imaging (DWI), and clinical outcomes between patients with and without AF (AF and non-AF groups). RESULTS: A total of 464 patients (292 men; mean age 68.5 ± 13.2 years) were registered. Of these, 79 patients (17%) had AF. Patients in the AF group were older (73.9 ± 9.1 vs. 67.4 ± 13.6 years, p < 0.001) and more likely to show disturbance of consciousness (13 vs. 6%, p = 0.046) and aphasia (9 vs. 3%, p = 0.007) than patients in the non-AF group. Although no difference in the overall DWI-positive rate was seen between the groups (28 vs. 20%, p = 0.102), a single lesion (23 vs. 10%, p < 0.001), a lesion ≥15 mm (11 vs. 4%, p = 0.006), and a single lesion ≥15 mm (11 vs. 2%, p < 0.001) on DWI were more frequent in the AF group. Multivariate logistic regression analysis identified increased age [odds ratio (OR) 1.04; 95% confidence interval (CI) 1.02-1.07] and DWI single lesion ≥15 mm (OR 5.67; 95% CI 1.92-16.7) as independently associated with the presence of AF. CONCLUSIONS: In this study, 17% of our TIA patients had AF. We found an association between the acute ischemic lesion pattern on DWI of a single lesion ≥15 mm and AF in TIA patients. These results might lead to a better diagnosis of TIA patients with AF.